The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1152/ajprenal.00180.2012
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR-inhibitor rapamycin mediates proteinuria in nephrotoxic serum nephritis by activating the innate immune response

Abstract: Rapamycin (Rapa) is an immunosuppressant used to prevent rejection in recipients of renal transplants. Its clinical use is limited by de novo onset or exacerbation of preexisting proteinuria. In the present study, Rapa administration was started 14 days after induction of murine nephrotoxic serum nephritis (NTS) to study glomerular effects of this mammalian target of rapamycin (mTOR) inhibitor. Glomeruli were laser-microdissected, and real-time PCR was performed to assess effects on glomerular cells and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…Interestingly, increased proteinuria has been observed with chronic treatment with everolimus, a derivative of rapamycin 32, 33 . In the present study, rapamycin treated rats exhibited 5-fold reduction of daily albumin excretion which was an even greater response than that found in SS CD247−/− rats 30 and tacrolimus treated rats 4 , which exhibited only a 3-fold reduction of daily albumin excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased proteinuria has been observed with chronic treatment with everolimus, a derivative of rapamycin 32, 33 . In the present study, rapamycin treated rats exhibited 5-fold reduction of daily albumin excretion which was an even greater response than that found in SS CD247−/− rats 30 and tacrolimus treated rats 4 , which exhibited only a 3-fold reduction of daily albumin excretion.…”
Section: Discussionmentioning
confidence: 99%
“…In many, though not all, situations the activation of innate immune cells leads to inflammation, which in controlled settings is host protective and can set the scene for adaptive immune response development. The administration of rapamycin in various inflammatory settings in vivo has shown that mTORC1 can either promote or inhibit inflammation, depending on the setting (Cejka et al, 2010; Kirsch et al, 2012), illustrating that the role of mTOR in innate immunity is complex and context dependent. In this section we will discuss the roles of mTORC1 and mTORC2 in the biology of innate immune cells.…”
Section: Mtor In the Innate Immune Systemmentioning
confidence: 99%
“…mTOR is present in two complexes, mTORC1 and mTORC2, which have distinct structure and function. In macrophages, mTORC1 has been shown to either promote or inhibit inflammation in a context‐dependent manner . In alternatively activated macrophages, mTORC1 was found to increase glucose metabolism and flux of carbon into the TCA .…”
Section: Alternatively Activated Macrophage Metabolismmentioning
confidence: 99%